RESPONSE OF BARLEY GENOTYPES TO PEG-INDUCED WATER STRESS AT SEEDLING STAGES - Muhammad Jawad Darwish; Sami Ullah Khan; Abdul Qayyum; Sajjad Khan; Zulfiqar Ali Gurmani (Journal of Animal and Plant Sciences, 2026)
Water stress negatively affects germination and seedling growth in barley, particularly during early developmental stages which are critical for crop establishment; however, divergent genotypes behave differently due to their divergent genetic makeup. To assess genotypic variations under water stress, thirty-five barley genotypes were evaluated under polyethylene glycol (PEG)-induced water stress conditions (0, 10, 20 and 30% PEG) at the Crop Sciences Institute, National Agricultural Research Center, Islamabad. Seeds were germinated in petri dishes, arranged in a completely randomized design, with three replications. Results revealed significant differences among genotypes and PEG levels for germination percentage, root, shoot, and coleoptile lengths (cm), and dry matter (mg). Increasing PEG concentration delayed germination and reduced all major growth attributes. Likewise, the seedling vigor index and coefficient of relative inhibition had different results for various genotypes. Pearson correlation analysis indicated strong positive associations among germination percentage, coleoptile length, seedling length, and vigor index, whereas the coefficient of relative inhibition was negatively correlated with these traits. Principal component analysis showed that the first two components explained 88.2% of total variance, with germination and seedling traits contributing maximum to PC1. Overall, genotypes NARC-01, NARC-04, NARC-06, NARC-07, NARC-10, NARC-13, NARC-14, NARC-16, NARC-17 and Sanobar-96 demonstrated superior water stress tolerance, suggesting their potential as parental lines for developing drought-resilient barley cultivars.
Keywords: Barley genotypes; polyethylene glycol; In-vitro conditions; drought stress; coleoptile length; seedling vigor index; coefficient of relative inhibition.